Refractory Dissolved Organic Matter has Similar Chemical Characteristics but Different Radiocarbon Signatures With Depth in the Marine Water Column - White, Margot E.; Nguyen, Tran B.; Koester, Irina; Lardie Gaylord, Mary C.; Beman, J. Michael; Smith, Kenneth L.; McNichol, Ann P.; Beaupré, Steven R.; Aluwihare, Lihini I. (Global Biogeochemical Cycles, 2023)
The >5,000-year radiocarbon age (14C-age) of much of the 630 ± 30 Pg C oceanic dissolved organic carbon (DOC) reservoir remains an enigma in the marine carbon cycle. The fact that DOC is significantly older than dissolved inorganic carbon at every depth in the ocean forms the basis of our current framing of the marine DOC cycle, where some component persists over multiple cycles of ocean mixing. As a result, 14C-depleted, aged DOC is hypothesized to be present as a uniform reservoir with a constant 14C signature and concentration throughout the water column. However, key requirements of this model, including direct observations of DOC with similar 14C signatures in the surface and deep ocean, have never been met. Despite decades of research, the distribution of Δ14C values in marine DOC remains a mystery. Here, we applied a thermal fractionation method to compare operationally defined refractory DOC (RDOC) from different depths in the North Pacific Ocean. We found that RDOC shares chemical characteristics (as recorded by OC bond strength) throughout the water column but does not share the same 14C signature. Our results support one part of the current paradigm—that RDOC is comprised of structurally related components throughout the ocean that form a “background” reservoir. However, in contrast to the current paradigm, our results are consistent with a vertical concentration gradient and a vertical and inter-ocean Δ14C gradient for RDOC. The observed Δ14C gradient is compatible with the potential addition of pre-aged DOC to the upper ocean.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022GB007603
Keywords: marine dissolved organic matter; radiocarbon; ramped pyrolysis oxidation